The Existence of Incompatience in Passport Manufacture Services Reviewed Through The Principles of Good Governance and Existing Regulations - Ikhsan Danandewa; Kirana Puspa Githa Zuliha; Mohammad Verdyansyah Surahman (IHSA Institute, 2022)
This study aims to analyze the existence of the principles of good governance and conformity with existing regulations regarding the process of making passports. This study uses a qualitative descriptive method with an empirical juridical approach. The empirical juridical approach is a literary approach that is guided by regulations, books or legal literature as well as materials related to the problems and discussions in writing this paper. The results of this study indicate that the implementation of passport services is still incompatible with existing laws such as Regulation of the Minister of Law and Human Rights Number 8 of 2014 concerning Ordinary Passport and Passport-like Travel Documents. This is proven where there are still immigration offices that do not mandate the rules that apply in the law.